Effect of Different Primings on Germination and Growth Parameters of Rice (Oryza sativa) Seeds during Drought Stress, as Compared with Silver Nanoparticles - Mahnaz Aghdasi; Pooyan MehrabanJoubani; Tahereh Nezamdoost; Fatemeh Tamaskani (پژوهش‌های بذر ایران, 2018)
The present study sought to compare the effect of seed priming by hydropriming, ascorbate and calcium chloride (CaCl2) versus different concentrations of silver nanoparticles on two Iranian rice cultivars (Hashemi and Shiroodi) under drought stress. The experimental design, which was factorial, was completely randomized. The first factor was control (without priming), hydro-priming, 20 mg.L-1 calcium chloride, 20 mg.L-1 ascorbates and 20, 40 and 80 mg.L-1 of silver nanoparticles. The second factor was the drought stress, including control, -1.48 and -4.91 bars created by polyethylene glycol 6000 solutions. In plants without drought stress, the time required to reach 50% germination (T50) reduced to 34 and 54 percent under ascorbate and CaCl2 priming in the Hashemi and Shiroodi cultivars, respectively.  In the drought stress condition, ascorbate and hydropriming pretreatments decreased T50 and the time required to reach 90% germination (T90) more than silver nanoparticles, especially in the Shiroodi cultivar. On the other hand, in comparison with other pretreatments, CaCl2 had an important role in increasing the growth factors in all of the drought stress treatments. Although 40 mg.L-1 silver nanoparticles increased the growth factors to some extent, it seems that higher levels of silver nanoparticles cause stress in seeds and therefore decrease the seed germination and growth of seedlings. By decreasing reactive oxygen species, Ascorbate improves the germination and by increasing plasma membrane efficiency, CaCl2 enhances the seedling growth under drought stress.